2019
DOI: 10.1007/s13730-019-00380-w
|View full text |Cite
|
Sign up to set email alerts
|

A case of apolipoprotein E Toyonaka and homozygous apolipoprotein E2/2 showing non-immune membranous nephropathy-like glomerular lesions with foamy changes

Abstract: A 47-year-old Japanese man with mild proteinuria was treated with an ACE inhibitor and antiplatelet agent for 7 years. However, urinary protein levels increased and renal biopsy was performed. Eight out of 20 glomeruli showed global or segmental sclerosis with foamy changes or bubbles, but with a different appearance to typical foam cells or lipoprotein thrombi. "Spike" formation, as observed in membranous nephropathy (MN), was segmentally detected in methenamine silver-stained sections.In an immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Seventeen variants in the APOE gene have been reported in lipoprotein glomerulopathy (LPG) (Table 1). Several variants were reported in single cases with various disease expression from the p.Arg132Cys in a normolipidemic patient with normal levels of apoE [77] to the p.Ser215Cys-E2/E2 in a type III hyperlipidaemic patient [78]. Four variants -p.Arg43Cys, p. Lys161_Arg165del, p.Arg168Cys, p.Arg168Pro -were reported in families with a dominant transmission and a reduced penetrance [79][80][81][82].…”
Section: Apoe and Lipoprotein Glomerulopathy (Lpg)mentioning
confidence: 99%
“…Seventeen variants in the APOE gene have been reported in lipoprotein glomerulopathy (LPG) (Table 1). Several variants were reported in single cases with various disease expression from the p.Arg132Cys in a normolipidemic patient with normal levels of apoE [77] to the p.Ser215Cys-E2/E2 in a type III hyperlipidaemic patient [78]. Four variants -p.Arg43Cys, p. Lys161_Arg165del, p.Arg168Cys, p.Arg168Pro -were reported in families with a dominant transmission and a reduced penetrance [79][80][81][82].…”
Section: Apoe and Lipoprotein Glomerulopathy (Lpg)mentioning
confidence: 99%
“…Immunoglobulin and complement depositions were not specifically obsereved in immunofluorescence studies. Unlike the case reported by Fukunaga et al, 44 foam cells characteristic of apoE2 homozygote glomerulopathy and non-lamellated lipoprotein thrombi as reported by Sakatsume et al 20 were conspicuous in the cases reported by Hirashima et al 45 and Kato et al, 46 respectively. Therefore, in carriers exhibiting both apoE2 homozygote and apoE Toyonaka, the balance of non-immune MN-like lesions and apoE2 homozygote glomerulopathy may be dependent upon the influence of apoE Toyonaka within the hinge region.…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 60%
“…21 Membranous nephropathy-like apoE deposition disease (MN-like apoE disease). Recently, a new glomerular disease was identified in non-consanguineous carriers possessing the combination of apoE Toyonaka (Ser197Cys), a novel mutation, and apoE2 homozygote [44][45][46] (Figure 1). The first case reported by Fukunaga et al 44 was a 20-year-old female Japanese patient who underwent renal biopsy because she was found to have chance proteinuria and hematuria.…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ApoE2 homozygotes show glomerulopathy and lipoprotein thrombi [ 168 ]. ApoE2 has been associated with diabetic nephropathy with abnormal lipid metabolism.…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%